TRIBULUS TERRESTRIS METHANOLIC EXTRACT MODULATES SPIROTETRAMAT-INDUCED LIVER AND KIDNEY TOXICITY IN DOMESTIC PIGEONS (COLUMBA LIVIA DOMESTICA) - Salim Heddam; Cherif Abdennour; Meryem Nassar; Souheila Slimani; Ali Bouzekri (Journal of Animal and Plant Sciences, 2023)
This research aimed to examine the protective effect of Tribulus terrestris (TT) methanolic extract against Spirotetramat-induced (SPT) liver and kidneys toxicity in adult domestic pigeons. Thirty male pigeons weighing309.20 ± 14.41gwere divided equally into six groups and were treated orally as follows: (CT) was used as the control, the SPT group received 15 mg/kg BW/day of SPT, the TT100 and TT50 groups were administered 100 and 50 mg/kg BW/day of TT, respectively, in addition to (SPT+ TT100) and (SPT + TT50) groups. After ten consecutive weeks of treatment, pigeons were sacrificed, and their livers and kidneys were weighed and examined. Plasma was also analyzed for hepatic and nephrotic markers represented by alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), total proteins, urea, creatinine, glucose, and uric acid. The results showed that SPT administration induced a significant increase in liver and kidney weights, and plasma ALT, AST, GGT activities. The biochemical markers revealed increases in total proteins, urea, creatinine, glucose, and uric acid levels. However, the co-treatment of TT with SPT has restored liver and kidney weight, ALT, AST, GGT, and all other examined biochemical parameters. The histopathological examination showed necrotic and remarkable alterations in the liver and kidney tissues of the SPT group. However, combined treatment has reduced the hepatic and renal tissue injury induced by SPT alone. The present study demonstrated that TT possesses potential cytoprotective effects against hepato-nephrotoxicity caused by SPT.
Keywords: Tribulus terrestris; Spirotetramat; pigeons; liver; kidney